ENHANCING NATIONAL VALUES OF FUTURE PRIMARY SCHOOL EDUCATORS THROUGH DIGITAL PLATFORMS - Мустафаева, Қундыз (Журнал Педагогики и психологии в современном образовании, 2024)
In today's rapidly evolving educational landscape, the integration of technology has revolutionized teaching methodologies and learning approaches. With digital platforms becoming increasingly prevalent in educational settings, there is a growing opportunity to leverage these tools for the cultivation of national values among future elementary educators. This article delves into the multifaceted strategies and potential of utilizing digital platforms to instill and reinforce national values in aspiring elementary school teachers.